"Genesis and development of a scientific fact" An analysis in the light on its historical context - Mejía Escobar, Jorge Antonio (Estudios de Filosofía, 1991)
This paper presents Ludwik Fleck’s work Genesis and Development of a Scientific Fact, emphasizing those analytical concepts there developed which are more relevant to Philosophy and the History of science. Referring to the moment when the mentioned book was published, it also makes a presentation of the enlightened ethical component and of an epistemology of a biological nature that were present in the beginnings of the movement of the Vienna Circle and disappeared afterwards, leaving hardly any trace.